Nematode Management on Perennial Landscape Plants - William T. Crow (EDIS)
This document is ENY-051, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Publication date: April 2003.